2018
DOI: 10.21101/cejph.a5021
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis C virus genotypes and subtypes in Croatia: 2008-2015

Abstract: Objective: Hepatitis C virus (HCV) genotyping is an important part of pre-treatment diagnostic algorithms as it guides the choice of therapeutic regimens. The aim of this study was to analyse the distribution of HCV genotypes in patients with chronic hepatitis C from Croatia in the period 2008-2015. Methods: The study enrolled 3,655 anti-HCV positive patients with available results of HCV genotyping from the three largest national HCV genotyping laboratories. Results: The majority of HCV-infected individuals e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Anti-HCV antibodies were detected in 0.9% of individuals in 2010–2011 [ 15 ]. HCV genotypes were analyzed in patients with chronic hepatitis C in the period 1996–2005 and 2008–2015 [ 29 , 30 ]. There were no substantial changes in the molecular epidemiology of the two most frequent HCV genotypes in Croatia in the past 20 years.…”
Section: General Populationmentioning
confidence: 99%
“…Anti-HCV antibodies were detected in 0.9% of individuals in 2010–2011 [ 15 ]. HCV genotypes were analyzed in patients with chronic hepatitis C in the period 1996–2005 and 2008–2015 [ 29 , 30 ]. There were no substantial changes in the molecular epidemiology of the two most frequent HCV genotypes in Croatia in the past 20 years.…”
Section: General Populationmentioning
confidence: 99%
“…Previous studies of HCV epidemiology in Croatia were mainly focused only on the prevalence and distribution of various HCV genotypes and subtypes, while this study broadens this knowledge by including transmission and phylodynamic analyses. The most common HCV genotypes in the Croatian general population were found to be GT1 and GT3, with no major changes in molecular epidemiology in the last 20 years [ 12 , 31 ]. In this study, we observed higher median age of GT1b-infected patients (61 years) compared with GT1a (43 years) and GT3a (44 years), which is similar to data from a previous national study and could be attributed to predominantly iatrogenic mode of HCV transmission in GT1b which was significantly reduced in the last 30 years [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCV genotype distribution in Croatia varies according to different population groups and regions. Genotype 1 (GT1) is the most prevalent among the general population (57–80%), followed by genotype 3 (GT3) (13–48%), while the prevalence of genotype 2 (GT2) (1–2%) and 4 (GT4) (4–7%) is low [ 11 , 12 ]. HCV transmission via blood transfusion and unsafe medical procedures was significantly reduced after the introduction of blood donation screening for HCV in the 1990s [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019 HCV elimination was achieved in liver transplant patients. A plan for prevention and control of viral hepatitis is ready and waiting for the final approval by the Ministry of Health, so Croatian experts are optimistic regarding HCV elimination by 2030 [14,15].…”
Section: Discussionmentioning
confidence: 99%